A narrative approach for a client with irritable bowel syndrome. Issue 2 (1st May 2021) - Oshita, Yumi; Kamo, Kiyoshi; Gant, Larry
This article aimed to illustrate a new narrative approach that transformed a client's story of suffering by differentiating the meaning construction of a particular speech act of other people. The new narrative approach has fundamental roots in coordinated management of meaning theory. The authors reformed this as "modified coordinated management of meaning" (MCMM), and called the refined model the refined MCMM (RMCMM). The client was a 21-year-old woman who was diagnosed with irritable bowel syndrome (IBS) in high school. Her story of suffering concerned odors related to her IBS-diarrhea symptoms, which resulted in her experiencing difficulties in college life. The social worker intervened the client's meaning construction of the locutionary act of another person's speech act "something really stinks." The client acquired the skills for generating new meaning constructions and speech act selections to transform her story of suffering. The RMCMM was an efficacious narrative approach that allowed the client with IBS to transform her story of suffering over a short period.